Quantification of the novel N-methyl-d-aspartate receptor ligand [11C]GMOM in man. Issue 6 (June 2016) - van der Doef, Thalia F; Golla, Sandeep SV; Klein, Pieter J; Oropeza-Seguias, Gisela M; Schuit, Robert C; Metaxas, Athanasios; Jobse, Ellen; Schwarte, Lothar A; Windhorst, Albert D; Lammertsma, Adriaan A; van Berckel, Bart NM; Boellaard, Ronald
[ 11 C]GMOM (carbon-11 labeled N -(2-chloro-5-thiomethylphenyl)- N ′-(3-[ 11 C]methoxy-phenyl)- N ′-methylguanidine) is a PET ligand that binds to the N -methyl-d -aspartate receptor with high specificity and affinity. The purpose of this first in human study was to evaluate kinetics of [ 11 C]GMOM in the healthy human brain and to identify the optimal pharmacokinetic model for quantifying these kinetics, both before and after a pharmacological dose of S-ketamine. Dynamic 90 min [ 11 C]GMOM PET scans were obtained from 10 subjects. In six of the 10 subjects, a second PET scan was performed following an S-ketamine challenge. Metabolite corrected plasma input functions were obtained for all scans. Regional time activity curves were fitted to various single- and two-tissue compartment models. Best fits were obtained using a two-tissue irreversible model with blood volume parameter. The highest net influx rate (Ki ) of [ 11 C]GMOM was observed in regions with high N -methyl-d -aspartate receptor density, such as hippocampus and thalamus. A significant reduction in the Ki was observed for the entire brain after administration of ketamine, suggesting specific binding to the N -methyl-d -aspartate receptors. This initial study suggests that the [ 11 C]GMOM could be used for quantification of N -methyl-d -aspartate receptors.